Advancements in Copper Nanowires: Synthesis, Purification, Assemblies, Surface Modification, and Applications. Issue 26 (30th April 2018) - Zhao, Songfang; Han, Fei; Li, Jinhui; Meng, Xiangying; Huang, Wangping; Cao, Duxia; Zhang, Guoping; Sun, Rong; Wong, Ching‐Ping
Abstract: Copper nanowires (CuNWs) are attracting a myriad of attention due to their preponderant electric conductivity, optoelectronic and mechanical properties, high electrocatalytic efficiency, and large abundance. Recently, great endeavors are undertaken to develop controllable and facile approaches to synthesize CuNWs with high dispersibility, oxidation resistance, and zero defects for future large‐scale nano‐enabled materials. Herein, this work provides a comprehensive review of current remarkable advancements in CuNWs. The Review starts with a thorough overview of recently developed synthetic strategies and growth mechanisms to achieve single‐crystalline CuNWs and fivefold twinned CuNWs by the reduction of Cu(I) and Cu(II) ions, respectively. Following is a discussion of CuNW purification and multidimensional assemblies comprising films, aerogels, and arrays. Next, several effective approaches to protect CuNWs from oxidation are highlighted. The emerging applications of CuNWs in diverse fields are then focused on, with particular emphasis on optoelectronics, energy storage/conversion, catalysis, wearable electronics, and thermal management, followed by a brief comment on the current challenges and future research directions. The central theme of the Review is to provide an intimate correlation among the synthesis, structure, properties, and applications of CuNWs. Abstract : Copper nanowires (CuNWs) are highly attractive in a myriad of fields for their admirable structure, optoelectronic and mechanical properties, high electrocatalytic efficiency, and large abundance. This Review focuses on the latest advancements in structure, growth mechanism, purification, multidimensional assemblies, surface modifications, and emerging applications of CuNWs, aiming to realize the industrial applications of CuNWs.